Dual targeting of glutamine and serine metabolism in acute myeloid leukemia - Hameed, Kanwal M.; Bollino, Dominique R.; Shetty, Amol C.; Carter-Cooper, Brandon; Lapidus, Rena G.; Emadi, Ashkan (Frontiers in Oncology, 2024)
Acute myeloid leukemia (AML) is a heterogeneous hematological malignancy characterized by disrupted blood cell production and function. Recent investigations have highlighted the potential of targeting glutamine metabolism as a promising therapeutic approach for AML. Asparaginases, enzymes that deplete circulating glutamine and asparagine, are approved for the treatment of acute lymphoblastic leukemia, but are also under investigation in AML, with promising results. We previously reported an elevation in plasma serine levels following treatment with Erwinia-derived asparaginase (also called crisantaspase). This led us to hypothesize that AML cells initiate the de novo serine biosynthesis pathway in response to crisantaspase treatment and that inhibiting this pathway in combination with crisantaspase would enhance AML cell death. Here we report that in AML cell lines, treatment with the clinically available crisantaspase, Rylaze, upregulates the serine biosynthesis enzymes phosphoglycerate dehydrogenase (PHGDH) and phosphoserine aminotransferase (PSAT1) through activation of the Amino Acid Response (AAR) pathway, a cellular stress response mechanism that regulates amino acid metabolism and protein synthesis under conditions of nutrient limitation. Inhibition of serine biosynthesis through CRISPR-Cas9-mediated knockout of PHGDH resulted in a ~250-fold reduction in the half-maximal inhibitory concentration (IC50) for Rylaze, indicating heightened sensitivity to crisantaspase therapy. Treatment of AML cells with a combination of Rylaze and a small molecule inhibitor of PHGDH (BI4916) revealed synergistic anti-proliferative effects in both cell lines and primary AML patient samples. Rylaze-BI4916 treatment in AML cell lines led to the inhibition of cap-dependent mRNA translation and protein synthesis, as well as a marked decrease in intracellular glutathione levels, a critical cellular antioxidant. Collectively, our results highlight the clinical potential of targeting serine biosynthesis in combination with crisantaspase as a novel therapeutic strategy for AML.